Broadly Neutralizing Anti-HIV-1 Monoclonal Antibodies in the Clinic - Caskey, Marina (Nat Med, 2019)
Combination anti-retroviral therapy (ART) has revolutionized the treatment and prevention of HIV-1 infection. Taken daily, ART prevents and suppresses the infection. However, ART interruption almost invariably leads to rebound viremia in infected individuals due to a long-lived latent reservoir of integrated proviruses. Therefore, ART must be administered on a lifelong basis. Here we review recent preclinical and clinical studies that suggest that immunotherapy may be an alternative or an adjuvant to ART because in addition to preventing new infections, anti-HIV-1 antibodies clear the virus, directly kill infected cells and produce immune complexes that can enhance host immunity to the virus.